Probing the conserved roles of cut in the development and function of optically different insect compound eyes - Rathore, Shubham; Meece, Michael; Charlton-Perkins, Mark; Cook, Tiffany A.; Buschbeck, Elke K. (Frontiers in Cell and Developmental Biology, 2023)
Astonishing functional diversity exists among arthropod eyes, yet eye development relies on deeply conserved genes. This phenomenon is best understood for early events, whereas fewer investigations have focused on the influence of later transcriptional regulators on diverse eye organizations and the contribution of critical support cells, such as Semper cells (SCs). As SCs in Drosophila melanogaster secrete the lens and function as glia, they are critical components of ommatidia. Here, we perform RNAi-based knockdowns of the transcription factor cut (CUX in vertebrates), a marker of SCs, the function of which has remained untested in these cell types. To probe for the conserved roles of cut, we investigate two optically different compound eyes: the apposition optics of D. melanogaster and the superposition optics of the diving beetle Thermonectus marmoratus. In both cases, we find that multiple aspects of ocular formation are disrupted, including lens facet organization and optics as well as photoreceptor morphogenesis. Together, our findings highlight a generalized role for SCs in arthropod eye form and function and define Cut as a central player in mediating these functions.